Microvascular free flaps are a safe and suitable training procedure during structured plastic surgery residency: a comparative cohort study with 391 patients - Hirche, Christoph; Kneser, Ulrich; Xiong, Lingyun; Wurzer, Paul; Ringwald, Felicitas; Obitz, Franziska; Fischer, Sebastian; Harhaus-Wähner, Leila; Gazyakan, Emre; Kremer, Thomas (Journal of plastic, reconstructive & aesthetic surgery, 2016)
Background - Microvascular free flaps have become a reliable standard procedure. Due to increasing microsurgical experience in teaching hospitals, residents are getting acquainted with performing free flap surgeries earlier in their training. However, economic considerations and safety regulations contradict adequate teaching. A validation of procedures for residency training is necessary to reduce the existing concerns. - Methods - This retrospective, comparative cohort study was designed to investigate whether free flaps are a safe residency training procedure. In addition, the aim was to establish standards for microsurgical training. Between 2008 and 2011, 391 patients were included who underwent reconstructive surgery with free flaps, under the supervision of either an experienced microsurgeon (cohort 1) or a resident in training (cohort 2). Patient demographics, interventional characteristics, as well as outcome parameters were attributed for comparative analysis. - Results - The comparison of both cohorts revealed a significant difference for defect cause (p < 0.01) and defect localization (p < 0.001). Free flaps for breast reconstruction were more frequently used in cohort 1, and ALT flaps were more used in cohort 2 (p < 0.001). The length of hospital stay was significantly reduced in cohort 1 (p < 0.001). No significant differences for major postoperative complications were identified. - Conclusion - With respect to standardized environmental conditions and risk stratification, microvascular free flaps can be applied as a safe training procedure during residency. Adequate teaching conditions require a sufficient case load and a high level of expertise of the teacher. The resident's experience and skills as well as the institutional infrastructure and expertise require consideration. Level of evidence: III.
Gesehen am 14.05.2020